2015
DOI: 10.1039/c4sc03839h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a C–C double bond from two aliphatic carbons. Multiple C–H activations in an iridium pincer complex

Abstract: Iridium can mediate a reversible intramolecular coupling reaction involving up to four unactivated Csp3–H bonds, to give a carbon–carbon double bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 57 publications
6
50
0
Order By: Relevance
“…In line with our previous studies, [2] DFT calculations showed that the isomerization of 2 to 3 begins with an aelimination of ahydrogen atom to give Ir carbene 7,followed by migratory insertion of the carbene moiety into the IrÀC bond (Scheme 5). Other possible mechanisms are prohibitively high in energy.T he iridium(I) complex resulting from C À Cr eductive elimination could not be located.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…In line with our previous studies, [2] DFT calculations showed that the isomerization of 2 to 3 begins with an aelimination of ahydrogen atom to give Ir carbene 7,followed by migratory insertion of the carbene moiety into the IrÀC bond (Scheme 5). Other possible mechanisms are prohibitively high in energy.T he iridium(I) complex resulting from C À Cr eductive elimination could not be located.…”
Section: Methodssupporting
confidence: 89%
“…Thereverse reaction, that is,the transformation of 3 into 7,i sm ore intriguing,a si tc orresponds to au nique aelimination of an alkyl group.W eh ave previously proposed this reaction type to be involved in C(sp 3 ) À C(sp 3 )b ond cleavage in arelated system, [2] but it has not been observed for completely unstrained systems thus far, nor have any detailed studies been reported. As the transformation of 2 to 3 is reversible,w ew ere,h owever, able to obtain kinetic and thermodynamic data for the reaction in both directions.T he enthalpic barrier for a-alkyl elimination was found to be comparable to that of a-hydrogen elimination (21.5 vs. 22.0 kcal mol À1 ), and the DG°value is only approximately 1kcal mol À1 larger.T he DFT calculated barriers are approximately the same.T hese results suggest that a-alkyl elimination reactions are fully possible for this and related systems from akinetic point of view,atleast when it comes to R 3 CÀM fragments.T hermodynamically,t he conversion of 2 into 3 is almost neutral with the equilibrium being slightly shifted towards 3,the C À Cbond-formation product.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported previously, 9 olefin complex 3 can be readily synthesized upon heating a benzene solution of hydridochloride 1 in the presence of base and tert-butylethylene as a hydrogen acceptor (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 98%